Troubling institutions. Issue 2 (14th November 2018) - Disney, Tom; Schliehe, Anna
Abstract : Institutions have troubled us for decades. Although the history of this engagement has been noted as somewhat "fragmented" (Billo & Mountz, 2015, Progress in Human Geography, 40, p. 199), geographers have engaged in detailed discussion on how to research institutions (Flowerdew, 1982, Institutions and geographical patterns, Croom Helm, London, UK), and noted their multifaceted and heterogeneous nature. In a special issue in 2000, Philo and Parr initiated a discussion on an emerging and wide ranging literature of institutional geographies and their epistemological frames. This collection seeks to invigorate institutional geographies in thinking through trouble and moving to develop "geographies of trouble." This special section on "Troubling Institutions at the Nexus of Care and Control" has emerged from three sessions at the annual conference of the RGS‐IBG in 2016. The papers reflect a diverse engagement with the institutional in geography and provide novel insights around the nature of trouble. We believe geographers could develop trouble, scaling up to map the interconnected circuits of trouble interventions but also to move forward and consider how these networks and institutions are changing, adapting and increasingly troubled themselves.